Supplementation of vitamin B12 or folic acid on hemoglobin concentration in children 6–36 months of age: A randomized placebo controlled trial. Issue 4 (August 2017) - Kumar, Tivendra; Taneja, Sunita; Sachdev, H.P.S.; Refsum, Helga; Yajnik, Chittaranjan S.; Bhandari, Nita; Strand, Tor A.; ,
Summary: Background & aims: The main objective of this report is to measure to what extent folate or vitamin B12 given daily for 6 months to young North Indian Children improves hemoglobin (Hb) concentration. Methods: In a randomized placebo controlled trial in low-to-middle income neighborhoods in New Delhi, India, children were randomized into four groups in a 1:1:1:1 ratio and supplemented daily for 6 months with 2 RDAs of vitamin B12, folic acid, both, or placebo. All children with anemia at baseline were given iron supplementation daily for 2 months. We measured the plasma concentrations of soluble transferrin receptor (sTfR), folate, vitamin B12, total homocysteine (tHcy) and Hb in 262 children. Results: Mean Hb concentration decreased in all four study groups during the six months of follow up and supplementation of either or both of the vitamins did not improve the Hb concentration. Iron supplements for the initial 2 mo had limited effect on anemia at 6 mo as almost 90% were still anemic at study end. Conclusion: Supplementation of folic acid and/or vitamin B12 for 6 months does not improve Hb concentration in young children. Our findings do not argue for widespread vitamin B12 or folic acid supplementation to combat anemia. Our results also call for alternative strategies to improve iron status and treat iron deficiency anemia. Clinical trial registry: NCT00717730 atwww.clinicaltrials.gov, CTRI No.: CTRI/2010/091/001090 atwww.ctri.nic.in .